Competition Effects of Purple Nutsedge (Cyperus Rotundus L.) on Growthand Yield of Tef[Eragrostis Tef (Zucc.) Trotter] in Ethiopia - Mohammed Sherif, Ahmed (2004)
Tef [Eragrostis tef (Zucc.) Trotter] is the staple food of Ethiopians, and purple nutsedge (Cyperus rotundus L.) is one of the commonest and most abundant weeds in tef. Thus, two experiments were undertaken at three locations, namely, Alem Tena, Debre Zeit and Tullu Bollo in Ethiopia to investigate competition effects of purple nutsedge on tef and determine combinations of seeding rates, sowing dates, fertilizer rates and time of weeding for effective control of nutsedge without the use of herbicides. The first experiment in each of the three locations consisted of three levels of tef seeding rates (10, 30 and 50 kg ha-1), fertilizer at rates of 0, 10 & 20 kg N ha-1 and 0, 10.5 & 21 kg P ha-1, in the form of Diammonium Phosphate (DAP) treatments, and nutsedge density (0, 30 and 60 plants m-2). The experiment was 33 factorial in a completely randomized block design with four replicates. The second experiment consisted of three sowing dates delayed by 0, 7 and 15 days and five weed removal treatments (no-weeding, weeded at 2, 4 & 6 weeks after crop emergence and a weed-free check). It was a 3x5 factorial in a completely randomized block design with four replications. The results obtained from this study indicated that tef was more competitive than nutsedge under conditions of stress at low soil fertility and high crop and weed densities. Tef plants under these conditions had fewer tillers, were much taller and produced higher yields. Highest seed rate of 50 kg ha-1 offered a greater competitive advantage to tef. The higher tef seeding rates were associated with higher biomass production, which was strongly and positively correlated with higher grain yield. Under conditions of higher soil fertility with applied fertilizer, purple nutsedge resulted in slightly more aggressive growth and reduced tef plant height and grain yield. A detailed analysis of the specific responses in tef plant height to nutsedge density and biomass in relation to fertilizer levels, tef seeding rates and nutsedge sowing densities showed that at the highest seed rate of 50 kg ha-1 tef was more competitive. There was a stronger trend in tef height increase with an increase in nutsedge density, and there was a strong positive correlation between tef plant height and grain yield (R2=0.75). The data also showed that conditions favoring increase in tiller production was associated with lower grain yield. Increase in panicle length was associated with an increase in spikelet numbers and a corresponding increase in tef grain yields, provided there was no delay in sowing. Sowing delays resulted in shorter panicles, and sowing delays of 7 and 15 days resulted in yield reductions of 59.60 and 68.39%, respectively. In general, tef was more competitive than purple nutsedge at all three experimental sites. In summary, crop seeding rates of between 30 and 50 kg ha-1, fertilizer rates of 10 & 20 kg N ha-1 and 10.5 & 21 kg P ha-1, and keeping the tef field free of weeds for at least six weeks and early sowing of tef would enhance farm yields. However, the prevailing environmental conditions may have also favored the survival and more aggressive growth of tef compared to nutsedge, probably due to the remarkable tolerance of tef to low moisture stress than nutsedge. Therefore, the competitiveness of tef against nutsedge needs to be further investigated under more favorable soil moisture conditions.